Wykorzystanie polityki bilansowej w zarządzaniu - Kaczmarek, Marcin (Policy of Preparing of Financial Reports in Management, 2007)
It should be stated that balance policy influences in a considerable way components value of a firm presented in reports. This influence translates into the assessment of firm's position by the receivers of information. The readers of reports should be aware of the fact that businessmen have possibilities to present the firm image which not always coincides with reality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 233-245